Association of composite dietary antioxidant index with mortality in adults with hypertension: evidence from NHANES - Qin, Huali; Shen, Li; Xu, Danyan (Frontiers in Nutrition, 2024)
Objective The objective of this study is to assess the correlation between composite dietary antioxidant index (CDAI) with all-cause mortality and cause-specific mortality in adults with hypertension. Methods The cohort study comprised adult participants with hypertension from the NHANES database, spanning 9 cycles from 2001 to 2018. Follow-up was conducted until December 31, 2019. Multi-variable Cox regression analysis was utilized to ascertain hazard ratios (HR) and their corresponding 95% confidence intervals, evaluating the relationship between CDAI and the risks of all-cause and cause-specific mortality. To further investigate the association between CDAI and mortality rates in adults with hypertension, Kaplan–Meier survival curves, restricted cubic splines (RCS), subgroup analyses and sensitivity analyses were employed. Results The analysis included 16,713 adults with hypertension (mean age 56.93 ± 0.23 years, 8,327 [49.61%] male). During the mean follow-up time 102.11 ± 1.22 months, with 3,908 (18.08%) all-cause mortality occurred, 1,082 (4.84%) cardiovascular mortality and 833 (3.80%) cancer mortality. Compared to the lowest quartile of CDAI, the weighted multivariate hazard ratios of participants in the highest quartile was 0.77 (95% CI, 0.68–0.87) for all-cause mortality, 0.83 (95% CI, 0.67–1.04) for cardiovascular mortality, and 0.64 (95% CI, 0.50–0.82) for cancer mortality. RCS analysis demonstrated a nonlinear association of CDAI with all-cause and cancer mortality, and a linear association between CDAI and cardiovascular mortality. The results were robust in subgroup analyses and sensitivity analyses. Conclusion Higher CDAI is associated with reduced all-cause mortality, cardiovascular mortality, and cancer mortality in hypertensive adults. Our findings highlight the importance of an antioxidant diet in improving outcomes in adults with hypertension.